Mapping of Fishing Areas and Fish Catches by Purse Sine KM. Rebert - Tinambunan, Deviana; Silooy, Fanny; Luasunaung, Alfret; Labaro, Ivor Lembondorong; Kayadoe, Mariana E; Sitanggang, Effendi Pengihutan; Thamin, arman; Dien, Heffry V (Jurnal Ilmiah Platax, 2022)
The division of Indonesian waters into several fisheries management areas illustrates very different habitat characteristics and has a diversity of biological resources that may vary. WPPNRI 716 is a management area in Indonesian waters which includes the waters of the Sulawesi Sea and the northern part of Halmahera Island. This research was carried out by the purse seiner KM. Rebert carried out fishing operations in the waters of the Sulawesi Sea at WPPNRI 716. Data collection was carried out for 4 months, namely from October 2021 - to January 2022, with the aim of knowing the distribution area of catching and KM. Rebert catches. KM. Rebet catchment area based on the GPS point is located at WPPNRI 716, which is 81.5 miles from the fishing base (Tumumpa Beach Fishery Port). The number of catches in October (trip 1) was 6350 kg, in October (trip 2) was 4807 kg, in November (trip 3) was 10245 kg, in December (tip 4), was 4234 kg, in December (trip 5) as much as 4280 Kg, in January (trip 6) as many as 2645, and in January (trip 7) 4350 Kg. Judging from the type of catch during the research, there was 13265 kg of mackerel scad (Decapterus sp), then 12953 kg of skipjack tuna (Katsuwonus pelamis L), 4884 kg of yellowfin tuna (Thunnus albacares), and 4100 kg of mackerel tuna (Euthinnus affinis). Selar fish (Selaroides sp) as much as 904 Kg, jackfish (Caranx sp) as much as 500 Kg, rainbow runner fish (Elagatis bipinnulatus) as much as 350 Kg, and the lowest is bullet tuna (Auxis rochei) fish as much as 55 Kg.Keywords: Mapping; KM. Rebert; Purse SeinerAbstrakPembagian wilayah perairan Indonesia ke dalam beberapa kawasan pengelolaan perikanan menggambarkan karakteristik habitat yang sangat berbeda dan memiliki keanekaragaman sumberdaya hayatinya yang dapat saja berbeda. WPPNRI 716 merupakan wilayah pengelolaan di perairan Indonesia yang meliputi perairan Laut Sulawesi dan sebelah Utara Pulau Halmahera.Penelitian ini dilaksanakan kapal pukat cincin (purse seiner) KM. Rebert yang melakukan operasi penangkapan ikan di perairan Laut Sulawesi pada WPPNRI 716.Â  Pengambilan data dilakukan selama 4 bulan yaitu pada bulan Oktober 2021 - Januari 2022, dengan tujuan untuk mengetahui daerah sebaran penangkapan dan hasil tangkapan KM. Rebert. Daerah penangkapan KM. Rebet berdasarkan titik GPS berada pada WPPNRI 716 yang berjarak dari fishing base (Pelabuhan Perikanan Pantai Tumumpa) Â± 81,5 mil. Jumlah hasil tangkapan pada bulan bulan Oktober (trip 1) sebanyak 6350 Kg, bulan Oktober (trip 2) sebanyak 4807 Kg, bulan November (trip 3) sebanyak 10245 Kg, bulan Desember (tip 4), sebanyak 4234 Kg, bulan Desember (trip 5) sebanyak 4280 Kg, bulan Januari (trip 6) sebanyak 2645, dan bulan Januari (trip 7) 4350 Kg. Dilihat dari jenis tangkapan selama penelitan adalah ikan layang (Decapterus sp) sebanyak 13265 Kg, kemudian ikan cakalang (Katsuonus pelamis L) sebanyak 12953 Kg, ikan tuna sirip kuning (Thunnus albacares) sebanyak 4884 Kg, ikan tongkol (Auxis rochei) sebanyak 4100 Kg ikan selar (Selaroides sp) sebanyak 904 Kg, ikan kuwe (Caranx sp) sebanyak 500 Kg, ikan sunglir (Elagatis bipinnulatus) sebanyak 350 Kg, dan yang paling rendah adalah ikan tongkol (Auxis rochei) sebanyak 55 Kg.Kata Kunci:Pemetaan; KM. Rebert; Pukat Cincin.Â